Influência de compostos inibidores na produção de etanol por Scheffersomyces (Pichia) stipitis ATCC 58376 - Leonel, Lillian Vieira (2014)
To supply the increasing demand for bioethanol it is necessary to search for new sources of renewable raw materials and emerging technologies. Most studies have been directed to the cellulose, since this fraction is more abundant in biomass and its hydrolysis leads to glucose, a more easily metabolizable sugar for the commercially available yeasts. Considering that the hemicellulose represents 20-30% of plant biomass and is easily removable, either by acid or enzymatic hydrolysis, the use of this fraction by pentose-fermenting yeasts as Scheffersomyces (Pichia) stipitis has been promising. However, the process of hydrolysis of lignocellulosic biomass to the release of fermentable sugars, specifically the acid hydrolysis, generates toxic compounds that impair the microbial metabolism and ethanol production. Thus, it is important to know the different effects of the major inhibitors present in hemicellulosic hydrolysates in the metabolism of S. stipitis ATCC 58376. For this purpose the culture was performed in synthetic medium supplemented with different concentrations of the inhibitors furfural, HMF, acetic acid, syringic acid and vanillin, following the Plackett and Burman factorial design with 12 assays (7 assays more compared to the number of independent variables) and 4 assays at the central point, totalizing 16 assays. The assays were conducted under agitation of 200 rpm at 30 °C and pH 5.25 for 96 hours. The analysis of the kinetic profiles obtained showed that the consumption of sugars, cell growth and ethanol production by S. stipitis were adversely affected by the addition of inhibitor compounds in synthetic medium promoting the inhibition of cell growth and ethanol production, as well as the delay in the consumption of sugars (xylose and glucose) according to the concentrations of the inhibitors tested. However, the acetic acid concentration of 2.0 g / L favored S. stipitis metabolism in the assays 09 (furfural 0.025 g.L-1; HMF: 0.01 g.L-1; acetic acid: 2.0 g.L-1, vanillin: 0.09 g.L-1 and syringic acid: 0.75 g.L-1), 10 (furfural: 0.75 g.L-1 HMF: 0,01 g.L-1; vanillin: 0.09 g.L-1 and syringic acid: 0.75 g.L-1) and 02 (furfural: 0.75 g.L-1; HMF: 0.03 g.L-1; acetic acid 2.0 g.L-1; vanillin: 0.09 g.L-1 and syringic acid: 0.025 g L-1), with peak concentrations of ethanol obtained in 72 hours of 14.3 g.L-1, 12.43 g.L-1 and 10.75 g.L-1, respectively, higher than the control assay (10.05 g.L-1), that lacked inhibitors. In assays with 6.0 g.L-1 of acetic acid, the metabolism of the yeast was completely inhibited. Statistical analysis for cell growth response showed that only acetic acid was significant (p < 0.10), being the most potent inhibitor. The others inhibitors also showed negative effect, except for syringic acid, which had a positive effect at 72 and 96 hours, but were not statistically significant. For the response ethanol production, among the factors evaluated, only the effect of furfural was not significant (p> 0.10). The most potent inhibitors were acetic acid and HMF, while vanillin and syringic acid promoted a positive effect on ethanol production. These results contribute to the choice of an appropriate method of detoxification for hemicellulosic hydrolyzate, which aims for a greater removal of the compounds that actually affect the metabolism of S. stipitis ATCC 58376